B-Learning y su influencia en el rendimiento académico en los estudiantes de la asignatura de Seminario de Tesis de la Facultad de Ingeniería de Sistemas e Informática de la Universidad Nacional de San Martín-Tarapoto - Paredes García, Gilberto (2012)
The investigación studies the influence that has the application of the the on-line and present mixed teaching pattern (B-Learning) in the improvement of the Academic Yield in the students.The investigation takes like sample to the students of the course of Seminar of Thesis of the Faculty of Engineering of Systems and Computer science of the National University of San Martín-Tarapoto. The investigation divided to the students in two groups, one experimental and another of control, in the experimental group the variable stimulus B-Learning was applied, implementing virtual classrooms for such effect, checking a homogeneous and significant improvement of the level of academic yield of this group, with relationship to the control group that worked with the model of present or traditional teaching, for what is deduced that the application of the teachingmodel B-Learning generates a bigger increment in the level of the academic yield with relationship to the model of traditional teaching.